“Under the Shadow of the Dog” – A New Monograph about the Golden Horde and Its Presence in the Balkans (Book Review: Aleksandar Uzelac. Pod Senkom psa. Tatari i južnoslovenske zemlje u drugoj polovini XIII veka [Under the Shadow of the Dog. Tatars and South Slavic Lands in the Second Half of the Thirteenth Century]. Belgrade, Utopija Publ., 2015. 324 p.+ 12 p. with color illustrations). - Dejan Radičević (Золотоордынское обозрение)
The article offers a critical review of the book of Serbian historian Aleksandar Uzelac, dedicated to the analysis of the relations between the Golden Horde and the Medieval Balkan Slavic states – Bulgaria and Serbia in the second half of the thirteenth century. The book is based on the wide corpus of Slavic, Latin, Byzantine and Oriental sources, archeological and numismatic findings, toponymy, as well as folklore tradition. The author offered a very insightful overview of the political relations between the Golden Horde and the Balkans, migratory movements of the populations from the Pontic Steppes to the Balkan region, and in addition he also dealt with the image of the Tatars in the eyes of its Christian contemporaries. The pivotal figure of the book is Nogai, whose career, status within the Golden Horde and achievements are analysed in detail. Moreover, armed with impressive erudition, the author challenged and revised many established misconceptions in Serbian and Bulgarian historiography. Another asset of the book is vivid and dynamic presentation of its contents, aimed not only at the specialists, but also the general audience. The shortcomings of this monograph are relatively few, with respect to omission of some archeological materials, but they do not diminish the general value of the monograph in question.